A Value-Added Service Analyzer (VaSA) sub-model for Agents of Things (AoT) concept - Mzahm A.M.; Ahmad M.S.; Tang A.Y.C.; Ahmad A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Internet of things; Robotics; Software agents; Internet of thing (IOT); Novel concept; Reasoning capabilities; Submodels; Value added service; Multi agent systems